2013
DOI: 10.1017/s0263574713000064
|View full text |Cite
|
Sign up to set email alerts
|

Manipulability analysis of human thumb, index and middle fingers in cooperative 3D rotational movements of a small object

Abstract: SUMMARYThe combined motion of the human thumb, index and middle fingers while rotating a small object across the extended, intermediate and flexed planes with respect to the fingers was analyzed. Auto reflective markers were attached on the fingers to track their motion across three postures and planes via a 3D motion capture system. Central, right and left rotation postures were considered in each plane for investigation and the rotation experiments were performed with 30 healthy subjects. The obtained data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The value of R p (t) which is a kinematic parameter varies significantly in magnitude and allows mostly positive values but is rarely negative which is satisfying the Orlando et al's [44] results. It has been concluded that human beings and robotic finger vary R p (t) in both magnitude and order with finger configuration.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The value of R p (t) which is a kinematic parameter varies significantly in magnitude and allows mostly positive values but is rarely negative which is satisfying the Orlando et al's [44] results. It has been concluded that human beings and robotic finger vary R p (t) in both magnitude and order with finger configuration.…”
Section: Discussionsupporting
confidence: 75%
“…al. [44], where the redundancy resolution is carried out for cooperative motion of the thumb, index and middle fingers in order to translate a small object along with maximization of instantaneous manipulability. Similar outcomes are recorded based on the Yoshikawa [9] inverse kinematics model which demonstrates analytically that the finest finger posture corresponds to the maximum value of the manipulability measure.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that such models will help identify suitable algorithms for dynamic control in cases of coordinated translation tasks and free finger motion studied herein, and cooperative rotation manipulation explored elsewhere [Felix Orlando et al]. 56 This paper aims at providing a partial but crucial knowledgebase in finger motion that may assist in the design and development of, say, Electro-Encephalogram (EEG) or Electro-Myogram (EMG) based assistive devices in future.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, use of a generic open chain to universally represent the thumb is difficult. In our previous effort [Felix Orlando et al], 56 we used a five-dof model for the thumb with universal joints, each at the MCP and CMC locations. The disadvantage therein with the orthogonal and intersecting axes was that the model may not capture the torque transmission into the thumb tip forces accurately.…”
Section: Assumptions and Limitationsmentioning
confidence: 99%
“…Since human hand postures that hinder movement will affect performance, human manipulability might also be evaluated using robotic manipulability indices. Indeed, several researchers have reported the benefits of applying robotic manipulability indices to human movement (Chen et al 2010;Jacquier-Bret, Gorce, and Rezzoug 2012;Kanezashi et al 2008;Orlando et al 2013;Rezzoug et al 2012;Sasaki et al 2010;Seo, Matsui, and Doi 2008;Tanaka et al 2004;Yamazaki et al 2005;Yokogawa and Hara 2004). For upper limb movements, there was a correlation between the robotic manipulability index and results of human experiments (Seo, Matsui, and Doi 2008;Yamazaki et al 2005), and good upper limb posture for task execution could be predicted using this index (Kanezashi et al 2008;Yamazaki et al 2005).…”
Section: Introductionmentioning
confidence: 99%